SERVICE QUALITY, CUSTOMER VALUE, AND PRICE TO CONSUMER SATISFACTION AT KOPI KENANGAN COFFEE SHOP - Liliana Dewi; Shafamila Handininta Putri (Bajang Institute, 2022)
This research aims to analyze service quality, customer value, and price on customer satisfaction at Kopi Kenangan Shell. The quantitative method was used as the methodology with questionnaires as the data collection to 100 respondents. Data analysis used SPSS 25 with research testing techniques including validity, reliability, classical assumption, and multiple linear regression. The result found that service quality had a positive and significant effect on consumer satisfaction, as seen from the t count > t table (2,332 > 1,984). Price has a positive and significant effect on consumer satisfaction as seen from the t-test > t table (4,170 > 1,984) and service quality, customer value, and price have a positive and significant effect on customer satisfaction as seen from the regression equation Y = 0.656 + 0.348 X1 + 0.202 X2 + 0.316 X3. The research obtained the value of R square of 0.729 means that the independent variables in this study (service quality, customer value, and price) significantly influence the dependent variable (consumer satisfaction) of 72.9%.